THE ROLE OF MODERN INTERACTIVE TECHNOLOGIES IN RAISING THE LEVEL OF THE EDUCATIONAL PROCESS OF THE DEPARTMENT OF ANATOMY WITH CLINICAL ANATOMY AND OPERATIVE SURGERY OF POLTAVA STATE MEDICAL UNIVERSITY - Vorobyova , Kristina; Horodnycha , Alyona; Kobeniak , Mykola (Collection of scientific papers «ΛΌГOΣ», 2022)
The period of development and formation of the educational process has passed a huge path of improvement, and despite all the gains and formations, the path to improvement continues. First of all, it is connected with adaptation to a new world in which the level of development of technological capabilities is gaining more and more progress [1]. Modern youth from childhood has constant contact with the digital and virtual world, and therefore the educational process must adapt to such changes, because the future of the nation depends on progressive youth who will continue and improve the education systems of the state, especially in the medical field [2,3].